Glide path preparation with hand k-files and rotary pathfiles in curved root canals – an in vitro study - Stošić, Miljan; Geler, Katarina; Petrović, Violeta; Jovanović - Medojević, Milica (Medicinski podmladak, 2023)
Introduction: Preparation of glide path is an important precondition for safe use of rotary NiTi instruments during endodontic treatment. Aim: The aim of this study was to examine the duration of glide path preparation as well as all the changes in canal morphology and canal diameter after the application of hand K-files and NiTi rotary PathFiles. Materials and methods: This research was performed on the total of twenty Endo Training Blocks (Dentsply, Maillefer, Switzerland). The glide path was prepared using hand stainless steel K-files #10-15-20 (Dentsply, Sirona, USA) (n=10) and NiTi rotary PathFiles (Dentsply, Sirona, Switzerland) (n=10). The time required to establish the glide path was measured with an iPhone stopwatch (Apple Inc. Cupertino, California). The images of apical segment of canals before and after glide path preparation were taken under the stereomicroscope (Boeco BSZ-405, Germany), and then images were analyzed and processed with Scopeimage 9.0 (Teleskop, Austria). Statistical analysis was performed with Mann-Whitney test at the level of significance 5% (α=0.05). Results: A statistically significant difference was observed in terms of the time required for glide path preparation. The mean total time for glide path preparation was significantly longer with K-files (382 ± 62) than with PathFile (200 ± 11) (p <0.05). Statistically significant difference in terms of changing the morphology of the apical part of the canal (p>0.05) was not observed. The difference in diameter of root canal was at the limit of statistical significance (p≈0.05). Conclusion: Instrumentation with NiTi rotary PathFiles reduces the time required for glide path preparation. Preparing endodontic space for rotary instrumentation with hand K-Files and rotary PathFiles leads to similar changes in morphology of the apical segment. A slightly larger diameter of root canal was measured after preparation with the hand K-files.